Identification of Functionally Important TonB-ExbD Periplasmic Domain Interactions In Vivo - Ollis, Anne A. (American Society for Microbiology, 2012)
In Gram-negative bacteria, the cytoplasmic membrane proton-motive force energizes the active transport of TonB-dependent ligands through outer membrane TonB-gated transporters. In Escherichia coli, cytoplasmic membrane proteins ExbB and ExbD couple the proton-motive force to conformational changes in TonB, which are hypothesized to form the basis of energy transduction through direct contact with the transporters. While the role of ExbB is not well understood, contact between periplasmic domains of TonB and ExbD is required, with the conformational response of TonB to presence or absence of proton motive force being modulated through ExbD. A region (residues 92 to 121) within the ExbD periplasmic domain was previously identified as being important for TonB interaction. Here, the specific sites of periplasmic domain interactions between that region and the TonB carboxy terminus were identified by examining 270 combinations of 45 TonB and 6 ExbD individual cysteine substitutions for disulfide-linked heterodimer formation. ExbD residues A92C, K97C, and T109C interacted with multiple TonB substitutions in four regions of the TonB carboxy terminus. Two regions were on each side of the TonB residues known to interact with the TonB box of TonB-gated transporters, suggesting that ExbD positions TonB for correct interaction at that site. A third region contained a functionally important glycine residue, and the fourth region involved a highly conserved predicted amphipathic helix. Three ExbD substitutions, F103C, L115C, and T121C, were nonreactive with any TonB cysteine substitutions. ExbD D25, a candidate to be on a proton translocation pathway, was important to support efficient TonB-ExbD heterodimerization at these specific regions.